The Relationship Between the Level of Knowledge and Attitudes of the Community Regarding the Use of Family Medicinal Plants (TOGA) as An Optimization of Community Health - Isna Alfiyani; Abi Muhlisin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Family medicinal plants (TOGA) are a form of traditional medicine that has long been used by Indonesians to maintain health, but the level of knowledge and attitudes of the community towards their use still varies. This study aims to determine the relationship between the level of knowledge and attitudes of the community regarding the use of TOGA as an effort to optimize public health in Catur Boyolali Village. This study used a correlative descriptive design with a cross-sectional approach. The study population consisted of 40 members of the Catur Village germas group, selected using total sampling technique. Data were collected through knowledge and attitude questionnaires, then analyzed using Spearman Rank correlation test. The research instruments demonstrated content validity based on validation conducted in previous studies. The questionnaires met reliability criteria and showed good measurement consistency based on previous studies. Most respondents had a good level of knowledge (60%) and a good attitude (52.5%). The Spearman Rank test results showed a p-value of 0.901 (>0.05), which means that there is no significant relationship between the level of knowledge and attitude of the community towards the use of TOGA. There was no relationship between the level of knowledge and attitude of the community in the use of TOGA. The attitude of the community was influenced by other factors such as culture, experience, beliefs, and social support. Culture-based education and sustainable health promotion are needed to optimize the use of TOGA.